Rebel Trash, Bad Objects, Prison Hell. Issue 1 (27th July 2022) - Runions, Erin
Abstract : This essay explores connections between the expansion of the prison industrial complex and the evangelical debate about hell in the late twentieth century. It starts from the evangelical assertion that the Valley of Hinnom, from which the idea of Gehenna emerged, was a place for burning garbage and dumping the bodies of criminals. It traces this misguided "fact" through its reception history back to Isaiah 66:24 and to the trauma and loss of war that the interpretive tradition disavows. Isaiah 66 describes a favored heir at Jerusalem's breast and an expulsed group of rebels, following a strikingly similar trajectory to Melanie Klein's psychoanalytic object relations. The subject phantasizes violence toward those projected as persecutory bad objects that threaten safety. The essay argues that Klein's psychic structure, analyzed by critics as colonial, is resonant with evangelical discourses of hell, as well as with colonializing practices of waste management and incarceration. A close Kleinian reading of Isaiah 66 suggests that the final verse of eternal torment for rebels encodes a hyperbolic vilification and phantasy of violence toward the prophetic community's own bad objects. It proposes instead a more complex reading of the conflict animating the poetry and suggests that the text may be read reparatively as a negotiation of loss for both sides in a situation of trauma; it welcomes the heterodox community back into the fold. Following critics of environmental racism and the domestic warfare of incarceration, it argues for decolonizing reparations that recognize the needs and desires of those most affected by idealizations of safety that do great harm. Finally, it argues that there is no reparation without understanding that we are connected to our bad objects.